Linguistic capital and international circulation: A comparative study between Argentina, Brazil and Chile - Beigel, Fernanda (2022)
While the hyper centrality of English has been considered a central feature of the world academic system and an increasing tendency in the Latin American academic circuit, one that has been pushed by state scientific policies and by the beliefs of researchers, no attempt has been made so far to observe to which extent publication in English is indeed a requirement for developing an academic career in the region. We attempt to shed new light in this issue by exploring the results of a survey that compares the use of foreign languages in publications and the experiences of acquiring linguistic competence in English for researchers based in Argentina, Brazil and Chile. The results show a more complex reality than that advanced by the evidence of hyper centrality of English. Bibliodiversity and multilingualism seems to be more the norm than the exception among these researchers. A steady stream of publication in the national language was identified among them, as well as the use of other languages. As these results vary by disciplinary field and related to phd formation abroad, the article proposes a more nuanced view of the processes and dynamics of publication practices in the Southern Cone.